Power Laws in Firm Size and Openness to Trade : Measurement and Implications - Levchenko, Andrei (IMF Working Papers; Working Paper ;, 2010)
Existing estimates of power laws in firm size typically ignore the impact of international trade. Using a simple theoretical framework, we show that international trade systematically affects the distribution of firm size: the power law exponent among exporting firms should be strictly lower in absolute value than the power law exponent among non-exporting rms. We use a dataset of French firms to demonstrate that this prediction is strongly supported by the data. While estimates of power law exponents have been used to pin down parameters in theoretical and quantitative models, our analysis implies that the existing estimates are systematically lower than the true values. We propose two simple ways of estimating power law parameters that take explicit account of exporting behavior.